Development of a nucleic acid chromatography assay for the detection of commonly isolated rapidly growing mycobacteria. Issue 12 (8th December 2021) - Igarashi, Yuriko; Chikamatsu, Kinuyo; Sano, Sotaro; Miyamoto, Shigehiko; Aono, Akio; Osugi, Asami; Morishige, Yuta; Murase, Yoshiro; Yamada, Hiroyuki; Takaki, Akiko; Mitarai, Satoshi
Abstract : Introduction. Non-tuberculosis mycobacterium infections are increasing worldwide, including those caused by rapidly growing mycobacteria (RGM). Gap Statement. The identification of the aetiological agent in the context of infections is essential for the adoption of an adequate therapeutic approach. However, the methods for the rapid distinction of different RGM species are less than optimal. Aim. To develop a nucleic acid chromatography kit to identify clinically common RGM. Methodology. We tried to develop a nucleic acid chromatography kit designed to detect four RGM species (including three subspecies) i.e. Mycobacterium abscessus subsp. abscessus, Mycobacterium abscessus subsp. bolletii (detected as M. abscessus/bolletii ) Mycobacterium abscessus subsp. massiliense, Mycobacterium fortuitum, Mycobacterium chelonae and Mycobacterium peregrinum . The amplified target genes for each species/subspecies using multiplex PCR were analysed using a nucleic acid chromatography assay. Results. Among the 159 mycobacterial type strains and 70 RGM clinical isolates tested, the developed assay correctly identified all relevant RGM without any cross-reactivity or false-negatives. The limits of detection for each species were approximately 0.2 pg µl -1 . Conclusion. The rapid and simple nucleic acid chromatography method developed here, which does not involve heat denaturation, may contribute to the rapid identification and treatment of RGM infections.